Posttranslational regulatory system for nitrogenase activity in Azospirillum spp. - Fu, H A (1989)
The mechanism for "NH4+ switch-off/on" of nitrogenase activity in Azospirillum brasilense and A. lipoferum was investigated. A correlation was established between the in vivo regulation of nitrogenase activity by NH4Cl or glutamine and the reversible covalent modification of dinitrogenase reductase. Dinitrogenase reductase ADP-ribosyltransferase (DRAT) activity was detected in extracts of A. brasilense with NAD as the donor molecule. Dinitrogenase reductase-activating glycohydrolase (DRAG) activity was present in extracts of both A. brasilense and A. lipoferum. The DRAG activity in A. lipoferum was membrane associated, and it catalyzed the activation of inactive nitrogenase (by covalent modification of dinitrogenase reductase) from both A. lipoferum and Rhodospirillum rubrum. A region homologous to R. rubrum draT and draG was identified in the genomic DNA of A. brasilense as a 12-kilobase EcoRI fragment and in A. lipoferum as a 7-kilobase EcoRI fragment. It is concluded that a posttranslational regulatory system for nitrogenase activity is present in A. brasilense and A. lipoferum and that it operates via ADP-ribosylation of dinitrogenase reductase as it does in R. rubrum.